Towards European Transitions: Indicators for the Development of Marginal Urban Regions - Rubina Canesi; Giuliano Marella (Land, 2022)
Urban transitions and urban-scape have been heavily impacted by the COVID-19 pandemic and will likely be affected by the current Ukrainian-Russian conflict. These two major events have affected European urban regions and especially marginal regions. Indeed, these regions are mostly struggling with inequality, lack of optionality, interoperability, and resilience due to their energy dependency and digital asymmetries. The continuous demand for a green and digital transition to strengthen social and economic resilience sought and targeted by the European Community has driven the policy of recent years to new European Guidelines. Nevertheless, the digital transition will require sustainability targets in the urban context, changing economic, social, and ecological relationships and balances. In this context, faced with these new transitions, marginal urban regions must plan, design, build, and manage future urban planning choices in a new digital-hybrid space. Therefore, it is crucial to support these transitions with a multi-dimensional sustainability concept through economic, environmental, social, and digital measurements. Urban sustainability indicators (USIs) play an essential role in supporting urban choices and planning. The current study analyzes recent literature and European standards to verify if and how they have changed in embracing the European Policy Pillar under a new and different sustainability profile, which needs to include digital sustainability. As a matter of fact, even if the concept of digitization has been recognized as a pillar of ongoing transitions, the literature and even European indicators struggle to recognize it as a tangible and measurable indicator of sustainability. Seeking to bridge the gap between European requirements and urban practice, the aim of this study is to identify and suggest new key indicators of digitalization to enable the digital sustainability of urban planning to be measured. These indicators can be used to implement a new valuation tool capable of supporting marginal regions by promoting sustainable urban investments in this new hybrid space.